2018
DOI: 10.4314/tjpr.v17i8.21
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin exerts anticancer effects on human cervical cancer cells via induction of apoptosis and regulation of Raf/MEK/ERK signalling pathway

Abstract: Purpose: To investigate the anticancer activity of apigenin on human cervical cancer cells. Methods: The anti-proliferative effects of apigenin on HeLa cervical cancer cells were determined by 3-(4,5-dimethylthiazol-2-yl)-)-2,5-diphenyltetrazolium bromide (MTT) and clonogenic assays, while its effect on apoptosis was assayed by DAPI and annexin V/PI double staining. Expression of proteins was assessed by immunoblotting. Results: Apigenin exerted anticancer effects on HeLa cervical cancer cells with an IC50 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Flavonoids are secondary metabolites corresponding to polyphenols that have a diverse structure, taking the form glycosides or aglycones in fruits and vegetables such as onions, berries, kale, and green tea [60]. Apigenin A recent study investigated the anti-proliferative effects of apigenin, an abundant flavonoid, on the human cervical cancer cell line HeLa [62]. Initial research demonstrated an IC 50 of 15 μMsimilar to that observed for some common chemotherapeutics.…”
Section: Flavonoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flavonoids are secondary metabolites corresponding to polyphenols that have a diverse structure, taking the form glycosides or aglycones in fruits and vegetables such as onions, berries, kale, and green tea [60]. Apigenin A recent study investigated the anti-proliferative effects of apigenin, an abundant flavonoid, on the human cervical cancer cell line HeLa [62]. Initial research demonstrated an IC 50 of 15 μMsimilar to that observed for some common chemotherapeutics.…”
Section: Flavonoidsmentioning
confidence: 99%
“…This was demonstrated by Western blot where apigenin increased the expression of Bax and decreased the expression of Bcl-2, commonly observed in apoptosis. The authors concluded that apigenin has apparent potential as a chemotherapeutic agent [62]. Erdogan et al [63] observed apigenin reduce prostate cancer stem cell survival and migration, via treating PC3 and cancer stem cells with a series of μM concentrations of apigenin for 48 hours.…”
Section: Flavonoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 4,6‐diamidino‐2‐phenylindole (DAPI) and Annexin V double staining techniques were applied for the analysis of the apoptosis in HeLa cells. The results indicated that apigenin reduced colony formation on HeLa cells and also induced apoptosis via habiting the Raf/MEK/ERK signaling pathway (Yang et al, 2018). Another study was performed to investigate the ability of apigenin in inhibition of self‐renewal capacity of sphere‐forming cells of HeLa cells and the results revealed the positive effects of apigenin in treatment of cervical cancer by reducing self‐renewal capacity of cells through the overexpression of casein kinase 2α (Liu et al, 2015).…”
Section: Contemporary Research On Promising Flavonoids Against Differ...mentioning
confidence: 99%